The Realism of Taxonomic Pluralism. (7th September 2020) - Lam, Ka Ho
In this paper, I present a critique of taxonomic pluralism, namely the view that there are multiple correct ways to classify entities into natural kinds within a given scientific domain. I argue that taxonomic pluralism, as an anti-essentialist position, fails to provide a realist alternative to taxonomic monism, i.e., the view that there is only one correct way to classify entities into natural kinds within a given scientific domain. To establish my argument, I first explain why the naturalist approach to natural kinds adopted by pluralists requires them to give up the mind-independence criterion of reality presupposed by monists. Next, I survey two types of pluralist account. I argue that, while the modest pluralist account is not pluralistic enough, the radical pluralist account fails to come up with an alternative criterion of reality that is robust enough to differentiate its position from anti-realism about natural kinds. I conclude by drawing out the implications of my critique for the essentialism/anti-essentialism debate about natural kinds.